Ureteral Stents Technology: Biodegradable and Drug-Eluting Perspective - Barros, A. A. (2017)
An ureteral stent is a versatile and indispensable common medical device in the management of several urological diseases. Nonetheless, the actual stent technology is far from the ideal. The ureteral stents available in the market are associated with clinical complications including bacterial adhesion, infection, encrustation development, pain and discomfort for the patients. Innovative stent materials and more research of new ureteral stent designs are necessary in order to avoid these complications and pursue the ideal stent, ie, a stent that can maintain the adequate urine flow from the kidney to the bladder and mitigation of hydronephrosis. In past years different approaches have been explored, including novel stent coatings, drug-eluting stent and biodegradable ureteral stents. The common goal of these new technologies is to increase the biocompatibility of the biomaterials and avoid the stent-related symptoms. New developments in ureteral stent field, namely drug-eluting biodegradable ureteral stents, are also envisaged to address new urological clinical scenarios. In summary there is no perfect ureteral stent that avoids all ureteral stent associated complications but there have been significant advances in last years in stent technology and particularly technologies such biodegradable drug-eluting stents are seen as very promising.